GAMBARAN DISIPLIN KERJA DAN KOMPENSASI BERPENGARUH PADA KEPUASAN KERJA KARYAWAN PDAM TIRTA BERKAH KABUPATEN - Afriyady, Moch Andry; Nuryanti, B Lena (Journal of Business Management Education (JBME), 2016)
Purpose: This study is to obtain findings regarding: Overview of labor discipline in the Regional Water Company PDAM Tirta Blessing Pandeglang, description of compensation for employees of PDAM Tirta Blessing Pandeglang, description of employee job satisfaction PDAM Tirta Blessing Pandeglang, amount of influence work discipline on employee job satisfaction Regional Water Company PDAM Tirta Blessing Pandeglang amount of influence compensation to employee satisfaction Regional Water Company PDAM Tirta Blessing Pandeglang amount of influence the discipline of work and compensation to employee satisfaction Local Company Blessing water PDAM Tirta PandeglangDesign/methodology/approach: Based on the level of explanation and research fields, then this type of research is descriptive and verification. Meanwhile, According Sugiyono (2013: 11) "Descriptive research is research conducted to determine the value of an independent variable, either one or more variables (independent) without making a comparison or connection between one and the other variables". Types and methods of research used the method used is explanatory survey which survey method is a method used to obtain data from a particular place is natural (not artificial), but the researchers did treatment in data collection, for example by circulating questionnaires, tests and structured interviews, with engineering samples saturated with a total of eighty-eight. The analysis technique used in this research is multiple linear regression with SPSS 20.0 softwareFindings: The findings of this study can be seen that the discipline of work and compensation has a positive and significant influence on employee job satisfaction with the level of correlation is very strong. Work discipline has a positive and significant impact on employee job satisfaction. And compensation has a positive and significant impact on employee job satisfaction.Originality/value: The findings of this study can be seen that the discipline of work and compensation has a positive and significant influence on employee job satisfaction with the level of correlation is very strong. Work discipline has a positive and significant impact on employee job satisfaction. And compensation has a positive and significant impact on employee job satisfaction. Based on these results is recommended as a basis for other studies done regarding the discipline of work and compensation with indicators and different objects.Â Keywords: Work Discipline, Compensation, Employee SatisfactionArticle Type: Article